Towards Cleaner Industry and Improved Air Quality Monitoring in Kazakhstan - World Bank (Washington, DC, 2014)
Kazakhstan's environmental situation is at a critical cross-road, where the pressures of economic growth without adequate environmental controls and the legacy of industrial production are beginning to take their toll on society in terms of health. In addition, Kazakhstan strives to promote itself as a modern and resource-efficient economy that is worthy of top international standing. In response, a series of proactive planning has emerged through such strategic initiatives as the Green Economy Concept with its accompanying actions that aim to reduce the ecological footprint of economic activities, promote sustainable economic growth and place Kazakhstan on a cleaner and greener development path. The document details the background and context of the situation in the country, and the initiatives that are being taken to improve air quality.